Sports-related acute shoulder injuries in an urban population - Are Hugo Pripp; Stefan Moosmayer; Martine Enger; Jens Ivar Brox; Stein Arve Skjaker; Lars Nordsletten; Knut Melhuus (BMJ Open Sport & Exercise Medicine)
Objectives More than a third of sports injuries involve the upper extremity. The primary aim was to quantify and describe sports-related shoulder injuries in a general population cohort. A secondary aim was to compare aspects of these injuries to those that were not sports-related.Methods We performed a prospective registration of the activity at the time of shoulder injury in all cases admitted during 1 year in a combined primary care and orthopaedic emergency department serving a defined population. The electronic patient records and patient reported questionnaires were reviewed.Results Twenty-nine per cent (n=781) of 2650 registered shoulder injuries were reported to be sports-related, with the highest proportion in acromioclavicular injuries (>50%). Patients with sports injuries were younger than those injured during other activities (median age 28 and 43 years, respectively, p<0.001), and more often male (78% and 52%, respectively, p<0.001). There was a strong gender disparity in incidence of sports-related shoulder injuries in adolescents and young adults, which was not observed in non-sports shoulder injuries. Football (soccer) (6–29 years), cycling (30–49 years), skiing (50–69 years) and martial arts were the dominating sports activities. Fractures were more common in skiing and cycling than in other major sports in the study.Conclusions Almost a third of the shoulder injuries occurred during sports. The types of sports involved varied with age and gender. The comparison of sport to non-sport shoulder injury incidence rates suggests that the increased risk of shoulder injuries in young males is mainly attributable to sports injuries.